Assessing the Impact of Liberalization of Trade Related Services on Services Growth in Pakistan - Maryam Mahfooz; Zafar Mahmood; Shabana Noureen (NUST Journal of Social Sciences and Humanities, 2021)
The services sector has offered sound support to Pakistan’s economic development. It has emerged as one of the fastest growing and highest contributing sectors of the economy. Through the use of Fully Modified OLS Estimation Technique, this study has provided evidence that liberalization of the two key sub-sectors (telecom and banking) of services of Pakistan has played an important role in development of these sectors. The task is achieved by preparing liberalization index for the two sectors. The econometric evidence reveals that results are robust and in accordance with the theory. Relationships are found to be relatively strong for the telecom sector and less strong for the financial sector. The research also shed light on the constraints that the country has to face in the liberalization process of these sectors. Rapid liberalization of the telecom sector has attracted substantial amount of investment, both local and foreign, and has created saturation in the industry, which has hampered further investment opportunities. This resulted in substantial decline of investment in this sector. But due to fast changing technologies, there is a possibility of it picking up again. By the increased liberalization of the telecom and banking services, the GDP of these sectors also increased. Hence, the full scale liberalization in the telecom sector evidently plays important role in growing the share of the services to economy’s GDP. Other economic indicators have also played an important role in defining the development of these sectors. Finally, a set of policy measures has been suggested to make the sector more effective and useful in accelerating the growth process.